2021
DOI: 10.1177/03000605211057866
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis of early surgery and conservative treatment in neonates and infants with severe hydronephrosis

Abstract: Objective The treatment strategy and timing of ureteropelvic junction obstruction (UPJO) in infants remain controversial. This study aimed to compare the effect of early surgical treatment (EST) and conservative treatment (CT) on neonates and infants with UPJO and their recovery of renal function and morphology. Methods Eighty neonates and infants with severe hydronephrosis were enrolled in this study. They received early pyeloureteroplasty or CT. Diethylenetriamine pentaacetate was used to assess renal functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Therefore, surgery is the preferred method for treating severe hydronephrosis. Studies by Deng et al (9) reported that during the diagnosis and treatment of severe hydronephrosis, EST can promote the recovery of renal structure and function, and CT may cause worsening of renal functions. In 2014, Policiano et al (10) reported that an APD of over 10 mm in the prenatal US is an indication of surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, surgery is the preferred method for treating severe hydronephrosis. Studies by Deng et al (9) reported that during the diagnosis and treatment of severe hydronephrosis, EST can promote the recovery of renal structure and function, and CT may cause worsening of renal functions. In 2014, Policiano et al (10) reported that an APD of over 10 mm in the prenatal US is an indication of surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Hydronephrosis induces distension of the renal pelvis and calyces, resulting in elevated intrarenal pressure. This pressure effect leads to cortical thinning, deformation of renal medulla blood vessels, activation of relevant inflammatory factors, and progressive renal parenchymal shrinkage, culminating in fibrosis [22,23]. Moreover, a prolonged duration of kidney exposure to hydronephrosis intensifies the degree of compression, resulting in worsened kidney morphology and function, ultimately leading to a poorer postoperative recovery outcome [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…This pressure effect leads to cortical thinning, deformation of renal medulla blood vessels, activation of relevant inflammatory factors, and progressive renal parenchymal shrinkage, culminating in fibrosis [22,23]. Moreover, a prolonged duration of kidney exposure to hydronephrosis intensifies the degree of compression, resulting in worsened kidney morphology and function, ultimately leading to a poorer postoperative recovery outcome [23,24]. Supporting evidence from animal experiments underscores this pathological transformation, affirming that the recovery after the resolution of urinary tract obstruction in mice depends on both the duration and severity of the obstruction [25].…”
Section: Discussionmentioning
confidence: 99%
“…Ureteral obstruction is a very serious clinical condition, leading to the damage of renal parenchyma because of obstruction-induced increased pressure, reduced glomerular filtration, activation of profibrotic factors, cell apoptosis, and subsequent loss of kidney function, which has been investigated in animal models in a series of studies [1,2]. Early recognition of obstruction, followed by timely treatment, usually results in the recovery of a kidney, mainly because of the better reproduction potential of renal stem cells and the recovery of parenchyma at an early age [3].…”
Section: Introductionmentioning
confidence: 99%